DIGITAL PLACEMAKING - Wilken, Rowan; Humphreys, Lee; Polson, Erika; Norum, Roger; Witteborn, Saskia; Halegoua, Germaine; Frith, Jordan; Richter, Jacob (AoIR Selected Papers of Internet Research, 2020)
This panel introduces and critically examines the concept of "digital placemaking" as practices that create emotional attachments to place through digital media use. As populations and the texts they produce become increasingly mobile, such practices are proliferating, and a striking array of applications and uses have emerged which exploit the affordances of mobile media to foster an ability to navigate, understand, connect to, and gain a sense of belonging and familiarity in place. The concept of digital placemaking is both a theoretical and applied response to the spatial fragmentation, banal physical environments, and community disintegration thought to have accompanied the speed and scale of globalization—the implications of which include suggestions that our collective sense of place has been disrupted, leaving people unsure of their belonging within conditions and boundaries that seem increasingly fluid. While it is imperative to attend to the shifting social, economic, and political conditions that give rise to such concerns, it is also necessary to recognize the many ways people actually use digital media to negotiate differential mobilities and become placemakers. Papers in this interdisciplinary panel consider digital placemaking through a range of perspectives investigating lived experiences of assorted communities with disparate social and economic power to demonstrate how digital media can facilitate social and geographic boundary crossing while encouraging new ways of placing ourselves—symbolically, virtually, or through co-located presence.